SATUAN PERLINDUNGAN MASYARAKAT (Jurnal Konstituen, 2021)
This articel is about the Public Protection Unit (Satlinmas) formerly known as civil defense (Hansip). This article is a summary of the results of the desk study and fieldwork conducted in October-November 2013 in the town of Magelang and Surabaya. This study used descriptive qualitative approach to explore the combined role and existence Satlinmas. The results of the study showed, the existence of the problem Satlinmas still leave many, including, first, the legal basis for the establishment of Satlinmas. Until now, there has been no new regulations governing Satlinmas. Existing regulations are too weak and can not capture the times. Second, the formulation of concepts and basic tasks and functions Satlinmas overlap with other institutions. Third, Satlinmas image in society tend to fade and abused. Fourth, Satlinmas incorporation into the Municipal Police deemed not appropriate, because different philosophy.Keywords: public protection unit, civil defence, natural disasters, peace and order society, and environmental safety systems